2022
DOI: 10.53365/nrfhh/152273
|View full text |Cite
|
Sign up to set email alerts
|

Chemistry and pharmacological aspects of Aridanin, a lead compound from <i>Tetrapleura tetraptera</i> (Fabaceae)

Abstract: Aridanin, a triterpenoid N-acetylglycoside has been obtained from chemical investigations of the root of <i>Tetrapleura tetraptera</i>, a well-known seasoning spice from Cameroonian food. The structure of the compound has been established using its NMR data and by comparison of that data with the one reported in the literature. Further evidence has been compiled from literature and discussed on the occurrence, the extraction, isolation and analytical techniques as well as the reported biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 22 publications
0
0
0
Order By: Relevance
“…The presence of acridone alkaloids in C. grandis species is not a surprise, because that subclass of alkaloids is considered as the chemomarkers of Citrus. This work therefore brings a significant contribution to the chemotaxonomic knowledge of the species C. grandis, further identified here as a new source of aridanin (1) which was already reported from several other plant families (Sikam et al, 2023).…”
Section: Chemotaxonomic Significance Of This Studysupporting
confidence: 54%
See 2 more Smart Citations
“…The presence of acridone alkaloids in C. grandis species is not a surprise, because that subclass of alkaloids is considered as the chemomarkers of Citrus. This work therefore brings a significant contribution to the chemotaxonomic knowledge of the species C. grandis, further identified here as a new source of aridanin (1) which was already reported from several other plant families (Sikam et al, 2023).…”
Section: Chemotaxonomic Significance Of This Studysupporting
confidence: 54%
“…From the literature survey, we reported that aridanin (1) displayed some significant pharmacological activities including molluscicidal potency by reducing the level of glycogen of Biomphalaria glabrata during a period of exposure up to 4 weeks; while its antischistosomal potency was observed through the ability of the compound to diminish the transmission of schistosomiasis by dropping the cercariae production (Adewunmi et al, 1988;Adewunmi & Furu, 1989). Additionally, aridanin (1) also showed antibacterial, cytotoxic, trypanocidal and antiviral activities, which further support its importance in the development of new potent drugs (Sikam et al, 2023).…”
Section: α-Glucosidase Inhibitory Ac Vitymentioning
confidence: 75%
See 1 more Smart Citation